Cross-ethnic friendship and prosocial behavior's potential significance to elementary children's academic competence. Issue 1 (2nd January 2019) - Jutengren, Göran; Medin, Eva
ABSTRACT: The authors, with Swedish elementary school students ( N = 201), 9–12 years old, examined the potential significance to self-perceived academic competence of students' cross-ethnic friendship ties and prosocial behavior to better understand education's minority achievement gap. A crossed-lagged panel model was tested to investigate potential relationships between these variables over time, while controlling for temporal associations. The results revealed that higher levels of prosocial behavior were related to more positive academic performance six months later. However, higher levels of cross-ethnic friendship did not. The findings further establish the predictive influence of prosocial behavior on academic competence, indicating that this over-time relation is applicable also in the North European context, with its increasingly diverse ethnicity.